T helper cell- and CD40-dependent germline IgM prevents chronic virus-induced demyelinating disease - Gil-Cruz, Cristina (National Academy of Sciences, 2012)
Generation of antiviral IgM is usually considered as a marker of a short-lived initial antibody response that is replaced by hypermutated and more-efficient IgG. However, once viruses have established a particular niche for their persistence (e.g., within the CNS), the immune system has to specifically mobilize a broad range of antimicrobial effectors to contain the pathogen in the long term. Infection of the CNS with the mouse hepatitis virus (MHV) provides a unique model situation in which the extent of inflammatory CNS disease is determined by the balance between antiviral immune control, viral replication, and immune-mediated damage. We show here that whereas antibody- or B cell-deficient mice failed to contain MHV CNS infection and developed progressive demyelinating disease, germline IgM produced in activation-induced cytidine deaminase-deficient mice (aicda(−/−)) provided long-term protection against the chronic multiple sclerosis-like disease. Furthermore, we found that appropriate B-cell activation within the CNS-draining lymph node and subsequent CXCR3-mediated migration of antiviral IgM-secreting cells to the infected CNS was dependent on CD40-mediated interaction of B cells with T helper cells. These data indicate that the CD40-mediated collaboration of T and B cells is critical to secure neuroprotective IgM responses during viral CNS infection.